Nuclear fuel irradiation testbed for nuclear security applications - Wilson, Brandon A.; Conant, Andrew; Ulrich, Tashiema L.; Kercher, Andrew; Sadergaski, Luke R.; Gerczak, Tyler; Nelson, Andrew T.; Petrie, Christian M.; Harp, Jason; Shields, Ashley E. (Frontiers in Nuclear Engineering, 2023)
The nuclear security community has long been interested in the identification and quantification of nuclear material signatures to understand a material’s provenance, use, and ultimate application. New forensics signatures and methods intended for non-traditional or advanced nuclear fuel applications require fuel irradiation experiments to demonstrate viability and validity. Integral fuel irradiations have historically required significant costs and long timelines to design, irradiate, and characterize. This paper describes how a recently developed nuclear fuel irradiation testbed can be used to provide a low cost, rapid turnaround, modular test environment for irradiation and evaluation of nuclear fuel specimens for nuclear security applications. The irradiation testbed houses six small ‘MiniFuel’ samples within hermetically sealed capsules inside targets that can be removed in between each ~25-day operating cycle of the High Flux Isotope Reactor (HFIR). As many as nine targets can be irradiated using a single irradiation position (reflector region) in HFIR, allowing for varying irradiation temperatures and burnups. A suite of hot cell capabilities have been established to perform post-irradiation examination for measuring performance (e.g., fuel swelling, fission gas release) and facilitating experiment disassembly for subsequent property measurements, microstructural analysis, or chemical assay. This new testbed allows fuel irradiations to be conducted on an accelerated timeframe to enable rapid proof of concept testing and to provide reference material for nuclear fuel security applications. Recent applications using this testbed include the testing of isotopic taggants in UO2 fuel (intentional forensics), testing of U-10Mo fuel for down-conversion of highly enriched uranium--fueled reactors, and the production of irradiated UO2 fuel material for signature analysis of its isotopic composition (plutonium, fission gases, etc.).